Healthcare Monitoring Systems using Li-Fi Networks - PORSELVI S; BHAGYALAKSHMI L; SANJAY KUMAR SUMAN (Innovare Journal of Engineering and Technology, 2017)
Constant monitoring of patient's health condition in hospital is either manual or Wi-Fi based system. Wi-Fi based system is became slow in speed due to exponentially increased scalability. In this scenario, Li-Fi finds the places wherever Wi-Fi is applicable with additional features of high speed data network. Apart from the speed factor, Li-Fi is more suitable in hospital application for monitoring the patents' conditions without frequency interference with human body. This paper proposes an application of Li-Fi network in hospital for monitoring the patients' conditions such as temperature, pressure, heartbeat, glucose level and respiratory conditions by using respective sensors. The collected data from the sensors is transmitted to the sink and further these data are processed using microcontroller and sent to display unit in the form of graphs or charts. Based on the concept of visible light communication, a prototype model is built with the PIC microcontroller and basic sensors as peripherals and tested it's working. Thus the application of Li-Fi as a health monitoring system demonstrated experimentally.